Influence of carrier media physical properties on start-up of moving attached growth systems. (October 2018) - Dias, Joana; Bellingham, Mel; Hassan, Junaid; Barrett, Mark; Stephenson, Tom; Soares, Ana
Highlights: Three spherical and two cylindrical shaped carrier media were tested. Faster biofilm formation rates were observed with the spherical carrier media. Larger voidage of the spherical carrier media improved COD and ammonia removal. Carrier media physical properties and hydraulic efficiency played a role on start-up. Start-up was not a function of carrier media protected surface area. Abstract: Five carrier media with different shapes (spherical and cylindrical), sizes, voidage and protected surface areas (112–610 m 2 /m 3 ) were studied in a pilot scale moving bed biofilm reactor (MBBR). This study aimed at assessing start-up duration using biofilm formation rates. Results indicated that the spherical media required shorter periods to achieve stable biofilm formation rates associated with chemical oxygen demand (COD) (15–17 days), compared to cylindrical high surface area media (23–24 days). Protected surface area presented weaker correlations with the biofilm formation rate for COD (R 2 = 0.83) and ammonia removal (R 2 = 0.76). However, good correlations were observed with a combination of the media physical factors: dimensionality (Di), voidage (Voi), and hydraulic efficiency (HE) strongly correlated with biofilm formation rates for heterotrophic (R 2 = 0.95) and nitrifying bacteria (R 2 = 0.92). This study proposes that the media physical properties can contribute to shortening start-up, contributing to improved removal rates and fast commissioning of MBBRs.